A systematic review of quality improvement initiatives for continuous sedation until death. (April 2021) - Robijn, Lenzo; Deliens, Luc; Scherrens, Anne-Lore; Pauwels, Nele S; Pype, Peter; Rietjens, Judith; Chambaere, Kenneth
Background: Extensive debate surrounds the practice of continuous sedation until death within end-of-life care. Aim: To provide insight into existing initiatives to support the practice of continuous sedation until death and assess their feasibility and effectiveness. Design: Systematic review and narrative synthesis, registered on PROSPERO (CRD42020149630). Data sources: Records were searched through MEDLINE, EMBASE, CENTRAL, CINAHL, and Web of Science from inception to April 16 2020. Peer-reviewed studies reporting original data on initiatives to support the practice of continuous sedation were included for review. Results: Twenty-one studies met the criteria and were included. Initiatives were focused on assessment tools of consciousness and discomfort (9), the use of guidelines and protocols (8), and expert consultation (3). All initiatives were reported as useful, acceptable, and feasible. Studies on the use of monitoring devices showed that a small proportion of patients were found to be awake, despite the patient being unresponsive according to the observer-based sedation scales. However, the wide range of values of these monitoring devices for comfortable and adequately sedated patients seems to hamper its overall implementation in daily clinical practice. Physicians reported changes in practice conform to guideline recommendations but the shift was modest at best. Expert consultation was regarded as supportive when sufficient expertise is lacking and helpful in avoiding possibly unnecessary sedations. Conclusions: The reviewed initiatives may contribute to improvement of continuous sedation until death, though their evidence base is rather limited. More insight is needed into their feasibility, preconditions for effective implementation and impact in actual practice.